Voluntary wheel running reduces tumor growth and increases capillarity in the heart during doxorubicin chemotherapy in a murine model of breast cancer - Uurasmaa, Tytti-Maria; Ricardo, Chloé; Autio, Anu; Heinonen, Ilkka H. A.; Rundqvist, Helene; Anttila, Katja (Frontiers in Physiology, 2024)
Introduction: The possible beneficial effects of physical activity during doxorubicin treatment of breast cancer need further investigation as many of the existing studies have been done on non-tumor-bearing models. Therefore, in this study, we aim to assess whether short-term voluntary wheel-running exercise during doxorubicin treatment of breast cancer-bearing mice could induce beneficial cardiac effects and enhance chemotherapy efficacy. Methods: Murine breast cancer I3TC cells were inoculated subcutaneously to the flank of female FVB mice (n = 16) that were divided into exercised and non-exercised groups. Two weeks later, doxorubicin treatment was started via intraperitoneal administration (5 mg/kg weekly for 3 weeks). Organs were harvested a day after the last dose. Results: The tumor volume over time was significantly different between the groups, with the exercising group having lower tumor volumes. The exercised group had increased body weight gain, tumor apoptosis, capillaries per cardiomyocytes, and cardiac lactate dehydrogenase activity compared to the unexercised group, but tumor blood vessel density and maturation and tumor and cardiac HIF1-α and VEGF-A levels did not differ from those of the non-exercised group. Discussion: We conclude that even short-term light exercise such as voluntary wheel running exercise can decrease the subcutaneous mammary tumor growth, possibly via increased tumor apoptosis. The increase in cardiac capillaries per cardiomyocytes may also have positive effects on cancer treatment outcomes.